2016
DOI: 10.1002/hed.24475
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a comprehensive competency‐based transoral robotic surgery training curriculum with ex vivo dissection models

Abstract: This graduated curriculum provides a realistic training experience to develop competency with oropharyngeal resections before transition to the operating room. © 2016 Wiley Periodicals, Inc. Head Neck 38: First-1563, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…The curriculum was centered on robotic cadaveric dissection. Prior work has described TORS training for residents [13-15]; however, to our knowledge, this is the first report of a TORS residency curriculum with use of the actual robotic surgical system on human cadavers followed by assessment of TORS skills.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The curriculum was centered on robotic cadaveric dissection. Prior work has described TORS training for residents [13-15]; however, to our knowledge, this is the first report of a TORS residency curriculum with use of the actual robotic surgical system on human cadavers followed by assessment of TORS skills.…”
Section: Discussionmentioning
confidence: 96%
“…In comparison to the current study, Sobel et al [15] published their TORS curriculum in an ex vivo model in which performance was assessed by objective structured assessments of technical skills. In the future, an objective structured assessment of technical skills could be incorporated into our curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors evaluated 12 resident trainees as they performed a combination of virtual simulation tasks, three simulated oropharynx surgeries using a porcine model, and task‐trainer exercises. The authors found significant improvement in resident OSATS scores and margin status, but not resection time, between TORS‐naïve versus curriculum‐trained subjects …”
Section: Introductionmentioning
confidence: 94%
“…Robotic surgery training paradigms are not standardized and are highly variable . They commonly employ commercially available task trainers and virtual simulators to teach basic techniques for controlling an Intuitive Surgical (Sunnyvale, CA) da Vinci system.…”
Section: Introductionmentioning
confidence: 99%